Invasive candidiasis following lung transplant: An Assessment of impact utilizing a national insurance claims cohort - Kelly M. Pennington; Herb Heien; Hemang Yadav; Xiaoxi Yao; Bradley White; Steve G. Peters; Patricio Escalante; Che Ngufor; Raymund R. Razonable; Cassie C. Kennedy (PLoS ONE, 2025)
Introduction Lung transplant recipients (LTRs) are susceptible to invasive candidiasis (IC). This study aimed to assess the incidence, risk factors, and impact of IC on mortality in LTRs using a national insurance claims cohort. Methods We conducted a retrospective cohort study using administrative claims data from the OptumLabs® Data Warehouse. We identified LTRs from January 1, 2005, to December 31, 2023, using procedural codes. Exclusion criteria included re-transplantations and pre-transplant IC. We employed multivariable logistic regression to identify risk factors for IC and Cox Proportional Hazard models to assess the impact of IC on mortality. Results Among 1279 LTRs, 131 (10.2%) developed IC, primarily during the initial hospitalization for lung transplantation (index hospitalization). The median time to IC diagnosis was 32.0 days following transplant. Post-transplant extra-corporeal membrane oxygenation (ECMO) for more than 8 days was associated with IC (OR: 2.34; 95% CI 1.03 to 5.34). Mortality was higher in LTRs with IC (HR: 2.31; 95% CI: 1.45 to 3.67; p < 0.001). LTRs with IC also had longer hospital stays (median 26.0 days vs. 20.0 days; p < 0.001) and more re-operations (36.7% vs. 27.3%; p = 0.003) compared to those without IC. Conclusion Invasive candidiasis affects approximately 10% of lung transplant recipients, most often during the initial hospitalization. It is associated with increased mortality, prolonged hospital stays, and a greater need for surgical re-intervention. These findings highlight the importance of early identification and targeted preventive strategies to improve outcomes in this high-risk population.